2001
DOI: 10.1089/088922201750461357
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Analysis of env C2/V3, gag p17/p24, and pol Protease Regions of 25 HIV Type 1 Isolates from Ho Chi Minh City, Vietnam

Abstract: Env C2/V3, gag p17/p24, pol protease, and RT regions of HIV-1 isolates recently obtained from 25 HIV-1 seropositive individuals from Ho Chi Minh City (Vietnam) were studied, and genes subtypes were determined by DNA sequence analyses. Twenty-three isolates out of 25 were identified as belonging to subtype E, now recognized as circulating recombinant form 1 (CRF01_AE). The motif at the top of the V3 loop (generally GPGQ) was then preceded by an isoleucine or a methionine (M) residue; the M residue might be a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The motif plays an important role in the V3 loop. 4,7,[11][12][13] Although the general effect of this mutation is still unknown, it has been suggested that changes in the crown tetrapeptide motif can greatly inhibit the binding of virus-neutralizing antibody. 10 Two closely related groups of subjects were identifi ed, each including several strains with insertions and deletions of specifi c amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…The motif plays an important role in the V3 loop. 4,7,[11][12][13] Although the general effect of this mutation is still unknown, it has been suggested that changes in the crown tetrapeptide motif can greatly inhibit the binding of virus-neutralizing antibody. 10 Two closely related groups of subjects were identifi ed, each including several strains with insertions and deletions of specifi c amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…Thai and US investigators using a less sensitive EIA (Vironostika-LS EIA, bioMérieux, France) to estimate the window periods of adults with recent infection, found significant differences between patients with subtype B and circulating recombinant form 1 (CRF01_AE) 9. Comparing our results from Ho Chi Minh City, where the dominant subtype is CRF01_AE,10, 11 with the much higher seroreversion rates observed in previous studies from South Africa and Malawi, where subtype C predominate,4, 7 raises questions about when the EIA would be a reliable tool to rule-out infection in HIV-exposed but uninfected Vietnamese infants.…”
Section: Discussionmentioning
confidence: 45%
“…However, there have been a few other studies describing HIV-1 genotypes in other regions of Vietnam such as Ho Chi Minh city, Hanoi and Hai Phong among similar cohorts. In all of them, CRF01_AE predominates although a few other subtypes have been identified such as B' [20] and some recombinants as CRF01_AE/B' [30], CRF02_AG/D [30] and CRF01_AE/C [31].…”
Section: Discussionmentioning
confidence: 99%